2016
DOI: 10.1186/s12885-016-2484-x
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin splice variants are differential predictors of breast cancer treatment responses

Abstract: BackgroundOsteopontin is a marker for breast cancer progression, which in previous studies has also been associated with resistance to certain anti-cancer therapies. It is not known which splice variants may mediate treatment resistance.MethodsHere we analyze the association of osteopontin variant expression before treatment, differentiated according to immunohistochemistry with antibodies to exon 4 and to the osteopontin-c splice junction respectively, with the ensuing therapy responses in 119 Polish breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…A major limitation of our study is that this is a retrospective study; our results should therefore be confirmed in validation cohorts, applying the OPN mRNA cut-off used the present study. In addition, protein expression of OPN splice variants should also be evaluated by immunohistochemistry, as suggested in a recent study by Zduniak et al [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major limitation of our study is that this is a retrospective study; our results should therefore be confirmed in validation cohorts, applying the OPN mRNA cut-off used the present study. In addition, protein expression of OPN splice variants should also be evaluated by immunohistochemistry, as suggested in a recent study by Zduniak et al [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although OPN is not tumor-specific, its potential as a tumor biomarker has been demonstrated in several malignancies, including breast cancer [ 3 , 4 ]. Elevated OPN expression has been associated with poor survival of cancer patients with different tumor histotypes [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The variants have distinct pathophysiological functions in cancer progression and convey distinct information on the disease. We have previously investigated the predictive capabilities of splice variants for treatment responses 8 and their prognostic potential for cancerous lesions. 9,10 A prior meta-analysis confirmed pan-Osteopontin to be correlated with premalignant progression in breast and other transformations.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of the autoantibodies was consistent with the appearance of splice variants in individual cancers. Breast cancer expresses OPN-a and -c, but not OPN-b (15,19,20). Liver cancer has elevated levels of OPN-a and -b, but not -c (14).…”
Section: Discussionmentioning
confidence: 99%